Untangling Entanglement - Stephanie H. Barclay (Washington University Law Review, 2020)
The Court has increasingly signaled its interest in taking a more historical approach to the Establishment Clause. And in its recent American Legion decision, the Supreme Court strongly suggested that the three-prong Lemon test is essentially dead letter. Such a result would make sense for the first two prongs of the Lemon test about secular purpose and the effects. Many scholars have observed that these aspects of the prong are judicial creations far afield of the Establishment Clause history. But what of the entanglement prong of the test? If we rejected all applications of this prong of the analysis, would we be essentially throwing the baby out with the bathwater? This Article cautions that this might be the case. A close analysis of the Court’s entanglement jurisprudence, compared against historical support for the various applications, suggests that entanglement jurisprudence ought to remain good law in at least two contexts. First, where it has protected religious groups from government interference with the autonomy, internal affairs, and administration. Second, where it prevents government from treating certain religious groups in a preferential way, including by granting monopoly power in the performance of public functions. On the other hand, the Court’s entanglement precedent is on far shakier historical ground in several contexts, including anti-sectarian skepticism of any sort of government aid to religious groups (and accompanying monitoring requirements to avoid religious use of funds), concerns about political divisiveness when government interacts with religious groups, and opposition to government classifications necessary to provide religious exemptions. If the Court were to modify its entanglement analysis to disregard ahistorical applications and embrace the historical ones, the upshot would be far less apparent tension between the Religion Clauses. Such an interpretation could facilitate an increase in religious pluralism and human flourishing and a decrease in unnecessary cultural fights aimed at excluding religion from the public sphere.
Keywords: Establishment clause; Entanglement; Religion clauses; Lemon test; Lemon v. Kurtzman 403 U.S. 602 (1971); American Legion v. American Humanist Association 139 S. Ct. 2067 (2019)